Midwives' experiences of managing women in labour in the Limpopo Province of South Africa - Sonto M. Maputle; D. H. Hiss (AOSIS, 2010)
Introduction:The objective of this study was to explore and describe the experiences of midwives managing women during labour at a tertiary care hospital in the Limpopo Province. An exploratory, descriptive, contextual and inductive design was applied to this qualitative research study. Purposive sampling was used to select midwives who were working in the childbirth unit and had managed women during labour. A sample of 12 midwives participated in this study. Data were collected by means of unstructured individual interviews and analysed through an open coding method by the researchers and the independent co-coder. Findings: Categories identified were lack of mutual participation and responsibility sharing, dependency and lack of decision-making, lack of information-sharing, empowering autonomy and informed choices opportunities, lack of open communication and listening, non-accommodative midwifery actions, and lack of human and material infrastructure. To ensure the validity of the results, criteria to measure trustworthiness were utilized. Conclusions: This study has implications for woman-centered care by midwives managing women in labour and provides appropriate guidelines that should be integrated into the Batho-Pele Principles.